Kajian Yuridis Asas Pembalikan Beban Pembuktian Dan Asas Actori Incubit Probatio - Melinda Putri Kumala (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
Abstract:The Principle of the Shifting of Burden of Proof is a burden of proof which’s place on one of the parties, that generally done by the public prosecutor. But in this case, the burden of proof was not done by the public prosecutor but placed on the defendant. In a case where the judge grants and validates the request from the defendant, which the defendant cannot prove dan show the application letter in front of the trial, a conflict arises with the application of the Principle of Reversed of the Burden of Proof in a civil lawsuit in comparison with The Principle of Actor Incubir Probatio. This journal will be reviewed by looking at the Civil Procedure Code, the Criminal Procedure Code, Herzien Inlandsch Reglament, Law 31 of 1999 concerning the Eradication of Corruption Crimes, as well as case studies, journals and other supporting reading materials. This journal is written for the purpose of using the principle of reversal of the burden of proof in civil procedural law and its legal consequences Keywords: The Principle of Reversed Burden of Proof, The Principle of Actori Incubit Probatio, Civil Procedural Law, Criminal Procedural Law Abstrak: Asas Pembalikan Beban Pembuktian merupakan suatu beban pembuktian yang diletakkan kepada salah satu pihak, yang umumnya dibebankan kepada penuntut umum. Namun dalam hal ini beban pembuktian tersebut diletakkan tidak lagi kepada penuntut umum namun terhadap terdakwa. Dalam suatu perkara dimana hakim mengabulkan dan mengesahkan permintaan penggugat yang tidak dapat membuktikan dan menunjukkan surat permohonan dimuka persidangan, maka munculah suatu pertentangan dengan dalam penerapan Asas Pembalikan Beban Pembuktian di suatu gugatan perdata yang juga dibandingkan dengan Asas Actor Incubir Probatio. Dalam jurnal ini akan dikaji dengan melihat Kitab Undang-Undang Hukum Acara Perdata, Kitab Undang-Undang Hukum Acara Pidana, Herzien Inlandsch Reglament, Undang-Undang 31 Tahun 1999 Tentang Pemberantasan Tindak Pidana Korupsi, serta, studi kasus, jurnal dan bahan bacaan pendukung lainnya. Jurnal ini ditulis dalam tujuan penggunaan Asas Pembalikan Beban Pembuktian dalam hukum acara perdata serta akibat hukumnya Kata Kunci: Asas Pembalikan Beban Pembuktian, Asas Actori Incubit Probatio, Hukum Acara Perdata, Hukum Acara Pidana